Adsorption dynamics of thermoresponsive microgels with incorporated short oligo(ethylene glycol) chains at the oil–water interface. Issue 25 (2nd June 2021) - Dan, Abhijit; Agnihotri, Priyanshi; Bochenek, Steffen; Richtering, Walter
Abstract : We report the effect of short OEG chains on the adsorption behaviour of thermoresponsive PNIPAM-based functional microgels at the oil–water interface at temperatures below and above the volume phase transition temperature of microgels. Abstract : Herein, we report a systematic study of the adsorption behaviour of short oligo(ethylene glycol) (OEG) chains incorporated into poly( N -isopropylaccrylamide) (PNIPAM) microgels at the dodecane–water interface as a function of the microgel concentration at two different temperatures: 298 and 313 K. The dynamic interfacial tension of the interface for the adsorption of these functional microgels is measured by means of a pendent drop method. We find that similar to pure PNIPAM microgels, the functionalized microgels initially get transported from the bulk to the interface, where they undergo the deformability dependent spreading process, and thus leading to a reduction of interfacial tension. However, the OEG chains significantly influence the dynamic processes of the microgels at the interface, enabling precise control over the interfacial activity. A tuneability of adsorption behaviour that is interpreted in terms of the diversity of structural and morphological features of the microgels, can be achieved by changing the temperature and/or the OEG chain length of the comonomer. While the temperature induced phase transition generally slows down the adsorption kinetics of the microgels, increasing the temperature from 298 to 313 K allows faster reduction of interfacial tension for the adsorption of the microgels with long OEG chains among the studied comonomers, making them a unique interfacially active functional material. Overall, incorporation of OEG chains allows tailoring the interfacial activity of microgels, thereby paving the way for the use of these microgels to act as effective Pickering emulsion stabilizers in a range of applications.